STUDENT’S PERCEPTION ABOUT ASSESSMENT RELATED WITH IMPLEMENTATION OF 2013 CURRICULUM - Octavianda, Regina P.; Rustaman, Nuryani; Sriyati, Siti (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2015)
ABSTRACTThe main focus of assessment is student, and how assessments are used will contribute to students’ perception. Students’ perception of assessment can be influenced by various types assessment, and Curriculum 2013 facilitate a variety of assessment for learning. Research about perception that involves 36 boys and 46 girls was conducted for identify students’ perception of assessment and the reconciliation with the demands of curriculum assessment in 2013. Data collected through the use of a questionnaire that was developed from perception indicators, i.e. reproducing knowledge, rehearsing, accountability, improving learning, problem solving, and critical judgement. This study placed improving learning perception in the first position and the rehearsing perception at the sixth position.About 85% of students consider that assessment can develop their knowledge, but only 52% of students consider that the assessment made them practice before the exam. Even though 2013 curriculum demands assessment which strongly supports six perceptions of students, in this study only few assessments criteria have been addressed. Research finding shows that only a few demands of the assessment has been completed. Therefore, high level of improving learning perception in this study is closely related to the reconciliation with the demands of Curriculum assessment in 2013 that involved types of assessments during the learning. ABSTRAKPengguna utama asesmen adalah siswa, dan penggunaan asesmen secara tidak langsung akan membentuk suatu persepsi. Persepsi siswa terhadap asesmen didukung oleh berbagai variasi asesmen, dan Kurikulum 2013 memfasilitasi penggunaan beragam asesmen dalam pembelajaran. Penelitian tentang persepsi ini melibatkan 36 siswa dan 46 siswi bertujuan untuk mengidentifikasi persepsi siswa terhadap asesmen dan kaitannya dengan tuntutan penilaian pada Kurikulum 2013. Data dikumpulkan melalui kuesioner yang telah dikembangkan dari indikator persepsi siswa yaitu reproducing knowledge, rehearsing, accountability, improving learning, dan critical judgment. Penelitian ini menempatkan improving learning pada posisi pertama dan rehearsing pada posisi terakhir. Sebanyak 85% siswa menyatakan bahwa asesmen dapat mengembangkan pengetahuan mereka, namun hanya 52% siswa yang sepakat bahwa asesmen membuatnya menjadi rajin berlatih sebelum menghadapi ujian. Walaupun tuntutan penilaian Kurikulum 2013 memfasilitasi keenam persepsi siswa terhadap asesmen, namun alam penelitian ini hanya beberapa jenis asesmen saja yang terlaksana. Hasil temuan membuktikan bahwa hanya beberapa tuntutan asesmen yang dilakukan. Oleh karena itu, tingginya persepsi improving learning dalam penelitian ini sangat dekat kaitannya dengan tuntutan penilaian pada Kurikulum 2013 yang digunakan selama pembelajaran.